U.S. population at increased risk of severe illness from COVID-19 - Ezimamaka Ajufo; Shreya Rao; Ann Marie Navar; Ambarish Pandey; Colby R. Ayers; Amit Khera (Elsevier, 2021)
Background: The U.S. Centers for Disease Control and Prevention (CDC) recognizes that older adults and individuals with certain medical conditions are at increased risk of severe COVID-19 infection. Understanding the proportion of the population at risk of severe infection, including among those with heart disease, could assist current vaccine strategy efforts. Methods: Using data from the 2015-2018 National Health and Nutrition Examination Survey (NHANES), we estimated the weighted prevalence of any of eight of eleven increased-risk conditions (including age ≥65) in U.S. adults aged ≥18 (N = 10,581) and extrapolated these results to a population of 233.8 million U.S. adults ≥18, and subgroups from the overall population defined by race/ethnicity, education, income and history of heart disease. Results: An estimated 176.1 million individuals representing 75.4% of U.S. adults had at least one increased-risk condition, 40.3% ≥2 and, 18.5% ≥3 conditions. Approximately 129 million adults aged <65 (69.2%) were also estimated to be at increased-risk. Compared to Whites, similar proportions of Blacks in the overall population (78.0 vs. 75.6%, p>0.05) and Hispanics in the younger population (70.8 vs 68.4%) were estimated to be at increased-risk. Conversely, a greater proportion of individuals with lower education and income levels were estimated to be at increased-risk both in the overall and younger population. In addition, an estimated 6.2 million individuals (14.5%) had heart disease. Among these, virtually all had at least one additional CDC risk factor (97.9%) and most had ≥2 or ≥3 risk factors (83.8% and 58.5%, respectively). Conclusions: As vaccination strategies are being explored, these results demonstrate that >75% of adults in the U.S. would be considered at increased-risk for severe COVID-19 infection by CDC criteria. Risk factor prevalence alone may not adequately capture the totality of risk, particularly among Black and Hispanic racial/ethnic groups and those with heart disease.